Survei Kepuasan Masyarakat Terhadap Implementasi Program Kebersihan, Keindahan, Dan Ketertiban (K3) Di Kota Mataram (Studi di Kelurahan Jempong Baru) - Hidayat, Rahmad; Ardyawin, Iwin; Mustamin, Mustamin; Mardiah, Mardiah (Lembaga Penelitian dan Pendidikan Mandala, 2021)
The Mataram City Government issued a Mataram City Regional Regulation (Perda) No. 10 of 2008 concerning waste management which aims to create a physically and mentally healthy society. A clean environment makes people healthy. A clean environment is part of faith. This will have an impact on the socio-cultural life of the city of Mataram with the motto of progress and religion, one of which is through service, empowerment and the role of the community in upholding improvement, cleanliness, and beauty (K3). One of the villages that implemented the program was Jempong Baru village. In this study the author aims to determine how the community's satisfaction with the implementation of the program of cleanliness, beauty and whether (K3) in Jempong Baru Village. A derivative of the Mataram City Regional Regulation concerning the implementation of the cleanliness, beauty and beauty (K3) program in Jempong Baru Village. In this study the authors analyzed the data with a simple survey method, and analyzed descriptively. From the total population, 50 respondents were selected as community leaders, youth leaders, and Jempong Baru village officials. Data was collected by using interview/interview methods, questionnaires and documentation. The results of the community satisfaction survey on the implementation of the K3 program in the Jempong Baru sub-district came to the conclusion that they were